Efeito da descarga de peso e da amplitude de movimento de flexão do ombro sobre a ativação muscular em condições estáticas e dos fatores ergonômicos e psicossociais durante atividade simulada de mouse em estudantes universitárias - Gonçalves, Josiane Sotrate (2015)
The movements adopted during computer activities and mobile devices contribute to musculoskeletal disorders. However, there is no consensus about safe range of motion and the effect of weight bearing to reduce overload. The objective of the first study was to evaluate the bilateral muscle activity of descending trapezius and anterior deltoid in different shoulder flexion postures in conditions with and without forearm support in the seated position. The hypothesis was that the forearm support reduce muscle overload compared to the no supported condition, and the reduction this overload would be higher for the greater shoulder flexion angles. Twentythree healthy university students aged between 18 and 31 years were evaluated. The sample size was determined a priori. The electrical activity of the upper trapezius and deltoid muscles were collected bilaterally. The weight bearing was assessed by load cells. A physical therapist positioned the shoulder of the participants at flexion angles of 0º, 15º, 30º, 45º, 60º in conditions with and without forearm support, in randomized order. The results showed that the forearm support reduced muscle activity in different shoulder flexion angles. The forearm support was more important than the shoulder posture to determine muscle overload. However, in this first study a computer task was not evaluated. Besides the forearm support, the modification of the workstation can lead to change in biomechanical exposure and it was not investigated. Another important risk factor is the stress, which can also contribute to neck/shoulder disorders. Thus, the purpose of the second study was to evaluate the effect of the work surface height, weight bearing and the difficulty of the task in the head, upper back and upper arms postures and the electrical activity of the descending portion of the trapezius and anterior deltoid during simulated mouse activity in university students. The study hypothesis was that the high table combined with the high difficulty activity level would result in greater biomechanical overload, i.e. at higher angles of head flexion, upper trunk and shoulders, increased electrical activity of the descending portion of the trapezius muscle and anterior deltoid. Furthermore, it was expected that the weight bearing on the table would reduce muscle activation. Fifteen healthy university students aged between 18 and 31 years were evaluated. The sample size was not defined a priori. The head and upper back flexion angles and the upper arms elevation were evaluated by inclinometers. Muscle activity was collected bilaterally and normalized by the maximal voluntary isometric contraction (MVIC). The weight bearing was evaluated by load cells and included as a covariate for muscle activation. In the simulated task, participants simulated mouse activity with the table at the elbow height (EH) and above the elbow height (AEH) in low (LD) and high difficulty levels (HD). Each condition was evaluated during five minutes in a randomized order. The results indicated that the table in the EH provided greater postural overload of the head and less overload to the shoulders and trapezius muscle. The HD level increased the head and upper back flexion angles. Thus, the head posture seems to be influenced by the table height and task difficulty; the upper back posture is related to the difficulty of the activity and the upper arms posture and trapezius activation were only influenced by table height. Therefore, this study revealed the effect of ergonomic and psychosocial risk factors on muscle activation and posture. The results highlighted the importance of these factors for understanding the risk associated with computer use.